Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1101/465914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein synthesis rates and ribosome occupancies reveal determinants of translation elongation rates

Abstract: Although protein synthesis dynamics has been studied both with theoretical models and by profiling ribosome footprints, the determinants of ribosome flux along open reading frames (ORFs) are not fully understood. Combining measurements of protein synthesis rate with ribosome footprinting data, we here inferred translation initiation and elongation rates for over a thousand ORFs in exponentially-growing wildtype yeast cells. We found that the amino acid composition of synthesized proteins is as important a dete… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(105 citation statements)
references
References 66 publications
6
98
1
Order By: Relevance
“…2E). Recently, Riba et al (23) found that the rate of protein translation can be impacted by amino acid composition of synthesized proteins as much as codon and transfer RNA adaptation. In particular, they show that negatively charged proteins are translated faster than positively charged protein.…”
Section: Resultsmentioning
confidence: 99%
“…2E). Recently, Riba et al (23) found that the rate of protein translation can be impacted by amino acid composition of synthesized proteins as much as codon and transfer RNA adaptation. In particular, they show that negatively charged proteins are translated faster than positively charged protein.…”
Section: Resultsmentioning
confidence: 99%
“…The less efficient translation initiation may have an essential role in the overall efficiency of the translation process. In yeast, for example, the relative inefficiency of translation of ribosomal proteins was suggested to at least partially stem from the positive charge of their protein products, which may interact more strongly with the negatively charged exit tunnel (Riba et al, 2019). Therefore, TOP elements may coordinate and optimize the rates of translation initiation and elongation to prevent potential collision of ribosomes and premature termination of translation (Racle et al, 2015).…”
Section: Iresmentioning
confidence: 99%
“…Although the average codon translation rate is rather constant transcriptome wide, estimated at 5.6 amino acid residues per second in eukaryotes, codon translation rates have been shown to vary up to 100-fold across a single transcript [8,9]. Many factors influence translation speeds across a single transcript (mRNA), including differences in cognate, near-cognate and non-cognate tRNA relative abundance, nascentchain charged residues inside the ribosome exit tunnel, mRNA secondary structure, proline residues at either A or P site of the ribosome, steric hindrance between contiguous ribosomes translating the same mRNA molecule, and the finite resource of the ribosome pool available in the cell [10][11][12][13][14][15][16][17][18][19][20][21][22]. The individual contributions of each of the previous factors to the rate of the translation are difficult to assess quantitatively and separately.…”
Section: Introductionmentioning
confidence: 99%